Environment-friendly water treatment ultrafiltration membrane and preparation method thereof
By preparing ultrafiltration membrane materials containing only carbon, hydrogen, and oxygen, the problems of high PVDF price and environmental pollution have been solved, resulting in high-performance and environmentally friendly water treatment ultrafiltration membranes suitable for industrial production.
Patent Information
- Application Number
- CN202210513428.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-05-11
AI Technical Summary
Existing water treatment ultrafiltration membrane materials such as PVDF are expensive and difficult to degrade, polluting the environment. Furthermore, biodegradable materials have poor membrane performance and cannot replace traditional membrane materials.
Ultrafiltration membranes are prepared by using thermoplastic polyester nonwoven fabric or inner lining tube containing only carbon, hydrogen, and oxygen elements in both the support layer and functional layer, and by esterification reaction of ethylene-vinyl alcohol copolymer. The degree of esterification and reaction conditions are strictly controlled, and pore-forming agents and surfactants are added to form a membrane structure with uniform pore size.
The prepared ultrafiltration membrane has performance comparable to that of traditional PVDF, but is low in cost. The waste membrane can be completely degraded into CO2 and H2O, without polluting the environment, making it suitable for industrial production.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water treatment ultrafiltration membranes, and specifically relates to an environmentally friendly water treatment ultrafiltration membrane and its preparation method. Background Technology
[0002] In the field of water treatment, ultrafiltration membranes can be used for reverse osmosis pretreatment in pure water and ultrapure water preparation processes; for separating bacteria, pyrogens, colloids, suspended impurities, and macromolecular organic matter in industrial water; and for purifying drinking water, mineral water, industrial wastewater, and domestic sewage. Ultrafiltration membranes can replace traditional water treatment processes such as natural sedimentation, plate and frame filtration, and activated carbon decolorization. Furthermore, the ultrafiltration process operates at room temperature, involves no phase change, and does not produce secondary pollution. Therefore, ultrafiltration membranes have a large customer base in the water treatment field.
[0003] In the field of water treatment, ultrafiltration membrane materials are mainly divided into two types: organic and inorganic. Organic materials, due to their wide variety, ease of processing, and excellent performance, have become the mainstream material for water treatment ultrafiltration membranes. Most organic materials are organic polymers, such as polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polysulfone (PSF), polyethersulfone (PES), chlorinated polyvinyl chloride (CPVC), and polytetrafluoroethylene (PTFE). Among these, PVDF, due to its excellent physicochemical properties and good membrane performance, has become the most widely used ultrafiltration membrane material on the market. PVDF is extensively used in hollow fiber membranes, flat sheet membranes, tubular membranes, and spiral wound membranes, and its products are covered by almost all well-known domestic and international ultrafiltration membrane companies.
[0004] PVDF is an important chemical raw material, used not only as a water-based membrane but also as a waterproof coating and lithium battery binder. Since 2021, influenced by factors such as supply and demand imbalances and short-term unpredictability, the price of PVDF, which had long been stable at around 100,000 yuan per ton, has surged. As of April 2022, the price of domestically produced PVDF coating grade was over 300,000 yuan per ton, water-based membrane grade was over 400,000 yuan per ton, and lithium battery grade was over 500,000 yuan per ton. Behind this price surge are two main factors: firstly, the surging demand from the lithium battery sector has impacted other downstream PVDF users; secondly, expanding PVDF production capacity is difficult due to the fact that PVDF's raw material, Freon-142b, severely pollutes the environment, especially the ozone layer. The Ministry of Ecology and Environment allocates production quotas for PVDF annually, and these quotas are decreasing year by year, ensuring that PVDF prices will remain high for the next few years. Another difficult problem with using PVDF in membrane products is the disposal of waste membranes. PVDF itself is difficult to degrade, and because it contains a large amount of fluorine, both landfilling and incineration will severely pollute the environment. Some companies have researched and made some progress in the recycling and reuse of waste PVDF membranes. However, the recycling cost is extremely high, and the recycled PVDF material contains impurities, and its molecular weight and molecular structure have changed. The performance of ultrafiltration membranes prepared from recycled PVDF is far inferior to that of new PVDF raw materials. Other traditional membrane materials have the same problems. For example, PVC and CPVC contain chlorine, and PSF and PES contain sulfur, which pollute the environment. Other materials, such as PP and PE, cannot be dissolved and processed into membranes using conventional solvents. They can only be prepared by melt processing, and the resulting membranes have relatively large pore sizes, usually microfiltration membranes.
[0005] To address the cost and environmental concerns associated with PVDF membrane materials, many companies are researching and using biodegradable materials for membrane fabrication. Patent CN 113457463 A discloses a biodegradable organic-inorganic composite membrane and its preparation method. This method uses ceramic as the base membrane, coats it with a biodegradable polylactic acid (PLA) coating, and then forms the membrane through NiPS and chemical cross-linking. Similar patents include CN 103157392 A and CN 111330456, all using PLA as the membrane material. Some also use cellulose as the membrane material (patent CN 107812453 A, etc.). While biodegradable materials solve environmental problems, the membranes made from them are far inferior to those made from traditional PVDF membrane materials in terms of mechanical strength and lifespan due to the ease with which the materials themselves degrade. Water treatment membrane manufacturers bear the heavy responsibility of environmental governance while facing the pressure of sustainable development; therefore, the development of new ultrafiltration membrane materials is both urgent and necessary. Summary of the Invention
[0006] The purpose of this invention is to provide an environmentally friendly water treatment ultrafiltration membrane and its preparation method. The special feature of this ultrafiltration membrane is that all its constituent materials, including the support layer and functional layer, contain only three chemical elements: carbon, hydrogen, and oxygen. Therefore, when this ultrafiltration membrane becomes waste after use, it can be incinerated like garbage to produce carbon dioxide and water, without harming the environment. This ultrafiltration membrane has good hydrophilicity and antifouling properties, and its other properties are comparable to traditional polyvinylidene fluoride ultrafiltration membranes. The preparation method of this ultrafiltration membrane is simple and easy to implement, suitable for industrial production. The prepared ultrafiltration membrane is not only environmentally friendly but also low in cost and highly economical.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] This invention first provides a method for preparing an environmentally friendly water treatment ultrafiltration membrane. The support layer of the ultrafiltration membrane is composed of a thermoplastic polyester nonwoven fabric or inner liner containing only carbon, hydrogen, and oxygen elements, and the functional layer is composed of a polymer containing only carbon, hydrogen, and oxygen elements. The preparation method includes the following steps:
[0009] S1: Ethylene-vinyl alcohol copolymer (EVOH) is used as a reaction raw material. It is heated and stirred in a solvent to dissolve it. Then, saturated fatty acids, catalysts and desiccants are added. Dry nitrogen gas is introduced and the temperature is raised to carry out an esterification reaction, generating a high molecular weight ester compound containing only carbon, hydrogen and oxygen elements. After the reaction is completed, all substances are filtered together through an activated carbon filter to remove the desiccant and impurities, and a clear and transparent high molecular weight ester compound solution is obtained.
[0010] S2: Add pore-forming agent and surfactant to the above polymer ester compound solution, stir evenly to obtain a clear and transparent casting solution, let the casting solution stand to remove bubbles and then use it.
[0011] S3: The above casting solution is coated onto a support layer composed of thermoplastic polyester nonwoven fabric or inner lining tube containing only carbon, hydrogen and oxygen elements to form a uniform liquid film. Then, it is placed in a coagulation bath and an ultrafiltration membrane is obtained through solution phase inversion. After rinsing with pure water, the ultrafiltration membrane is immersed in alcohol to remove residual pore-forming agents, surfactants, solvents, unreacted saturated fatty acids and catalysts. Then, it is naturally dried in the dark to obtain an environmentally friendly water treatment ultrafiltration membrane.
[0012] As a preferred embodiment of the present invention, the thermoplastic polyester is one of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).
[0013] As a preferred embodiment of the present invention, the ethylene molar content in the EVOH described in S1 is between 30% and 40%, and the melt index is less than 2 g / 10 min.
[0014] As a preferred embodiment of the present invention, the solvent mentioned in S1 is one of N,N-dimethylacetamide (DMAC) and N-methylpyrrolidone (NMP).
[0015] As a preferred embodiment of the present invention, the saturated fatty acid mentioned in S1 is one of lauric acid, palmitic acid, and stearic acid; the catalyst mentioned in S1 is one of p-toluenesulfonic acid, camphorsulfonic acid, and hydrochloric acid; and the desiccant mentioned in S1 is one of anhydrous sodium sulfate and 4A molecular sieve.
[0016] As a preferred embodiment of the present invention, the mass amounts of each substance used in the esterification reaction in S1 are as follows: 100 parts solvent, 20-23 parts EVOH, 3-5 parts saturated fatty acid, 0.2-0.5 parts catalyst, and 0.5-1 parts desiccant; the esterification reaction temperature is between 130 and 170°C, and the reaction time is 6-8 hours.
[0017] As a preferred embodiment of the present invention, the porogen described in S2 is one of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG); the surfactant is one of Tween-80 and Span-60; and the mass ratio of the porogen, surfactant and polymer ester compound solution is (2-3):(0.1-0.2):100.
[0018] As a preferred embodiment of the present invention, the coagulation bath described in S3 is pure water at 20-30°C.
[0019] This invention also provides an environmentally friendly water treatment ultrafiltration membrane prepared by the above-described method. The support layer of this ultrafiltration membrane is composed of a thermoplastic polyester nonwoven fabric or inner liner containing only carbon, hydrogen, and oxygen elements, and the functional layer is composed of a high-molecular polymer containing only carbon, hydrogen, and oxygen elements. The thickness of the ultrafiltration membrane is 80-120 μm. This ultrafiltration membrane not only possesses the performance of traditional PVDF ultrafiltration membranes but also has low cost and is easy to dispose of after becoming a waste membrane, without polluting the environment. Therefore, the support layer material of this invention uses PET and PBT because these two materials contain only carbon, hydrogen, and oxygen. This invention uses EVOH with an ethylene molar content between 30% and 40% and a melt index less than 2 g / 10 min as the reactant because EVOH is inexpensive, has good hydrophilicity, and contains a large number of hydroxyl groups (-OH) that can participate in the esterification reaction. Too low an ethylene content or too high a melt index results in insufficient material strength, while too high an ethylene content makes it difficult to dissolve and process with solvents. This invention uses DMAC and NMP as solvents because these two solvents have good solubility for the materials and their boiling points are above the esterification reaction temperature. The chemical reaction mechanism of this invention is as follows: the hydroxyl groups (-OH) of EVOH and the carboxyl groups (-COOH) of saturated fatty acids react under the action of an acidic catalyst to produce esters and water. To promote continuous reaction, a desiccant is added and dry nitrogen gas is introduced to remove the water generated in the reaction. The saturated fatty acids and catalyst used in this invention have good solubility and good reaction rates in the solvent of this invention. A small amount of surfactant is added to the casting solution of this invention to make the pore size more uniform after film formation.
[0020] The biggest challenge of this invention lies in the limits of the esterification reaction. The reason for using esterified EVOH as the membrane is that the EVOH material itself has relatively low strength. If it is used directly as a membrane, the mechanical strength will not reach that of traditional membranes. Furthermore, EVOH material is very soft, and membranes made directly from it are prone to shrinkage and deformation during the process of changing from a wet to a dry state, and the pores on the surface are easily collapsed. Therefore, esterification modification is necessary. However, if the esterification is too low, the desired effect will not be achieved. If the esterification is too high, there will be too few hydroxyl groups (-OH) in the membrane material, resulting in poor hydrophilicity of the membrane, which in turn will affect the membrane's antifouling properties. Therefore, the degree of esterification must be strictly controlled. The type and amount of solvent, catalyst, saturated fatty acid, and reaction conditions of the esterification reaction must also be strictly controlled.
[0021] The preparation method of this invention is simple and easy to implement, suitable for industrial production, and the prepared ultrafiltration membrane is not only environmentally friendly, but also low in cost and high in economic benefits, thus having broad market prospects. Detailed Implementation
[0022] To make the features and advantages of the present invention more apparent and understandable, a detailed description is provided below with reference to several specific embodiments and comparative examples of the present invention, so that those skilled in the art can have a more comprehensive understanding of the present invention. However, the scope and content of protection of the present invention are not limited to the specific embodiments disclosed below.
[0023] Example 1
[0024] Take 20g of Kuraray's H-171B EVOH (ethylene molar content 38%, melt index 1.8g / 10min) and add it to 100g of NMP. Heat and stir to dissolve. Then, add 3g of stearic acid, 0.2g of p-toluenesulfonic acid, and 0.5g of anhydrous sodium sulfate sequentially. After stirring evenly, purge with dry nitrogen gas and heat to 170℃. React for 6 hours. Then, filter all the substances together through an activated carbon filter to obtain a clear and transparent polymer solution. Take 100g of the polymer solution, add 2g of polyvinylpyrrolidone and 0.1g of Tween-80, stir evenly, and allow to stand to remove bubbles to obtain a clear and transparent casting solution. The casting solution is coated onto a PET inner liner tube to form a uniform liquid film, which is then placed in pure water at 20°C. After solution phase inversion, an ultrafiltration membrane with a thickness of 80 μm is obtained. The ultrafiltration membrane is rinsed with pure water and then soaked in alcohol to remove residual pore-forming agents, surfactants, solvents, unreacted saturated fatty acids, and catalysts. Then, it is naturally air-dried at room temperature in the dark to obtain the finished ultrafiltration membrane containing only carbon, hydrogen, and oxygen elements.
[0025] The ultrafiltration membrane prepared in Example 1 was tested, and its performance is as follows: the pure water flux at 20°C under a pressure of 0.1 MPa is 2000 L / m³. 2 The membrane has a bubble point of 0.12 MPa in water, a pure water contact angle of 12°, a PEG rejection rate of 92.5% for a molecular weight of 50,000 Da, and a bovine serum albumin rejection rate of over 99.8%. Elemental analysis shows that the membrane support layer contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 9 / 6 / 4, and the separation layer also contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 29 / 14 / 7. When the ultrafiltration membrane is burned in oxygen, analysis shows that the burning products are only CO2 and H2O.
[0026] Example 2
[0027] Take 23g of Kuraray's F-171 EVOH (ethylene molar content 32%, melt index 1.7g / 10min) and add it to 100g of DMAC. Heat and stir to dissolve. Then, add 5g of palmitic acid, 0.5g of camphor sulfonic acid, and 0.2g of 4A molecular sieve sequentially. After stirring evenly, purge with dry nitrogen gas and heat to 150℃. React for 7 hours. Then, filter all the substances together through an activated carbon filter to obtain a clear and transparent polymer solution. Take 100g of the polymer solution, add 3g of polyethylene glycol and 0.2g of Span-60, stir evenly, and allow to stand to remove bubbles to obtain a clear and transparent casting solution. The casting solution is coated onto PBT nonwoven fabric to form a uniform liquid film, which is then placed in a pure water coagulation bath at 30°C. After solution phase inversion, an ultrafiltration membrane with a thickness of 100 μm is obtained. The ultrafiltration membrane is then rinsed with pure water and soaked in alcohol to remove residual pore-forming agents, surfactants, solvents, unreacted saturated fatty acids, and catalysts. Finally, it is air-dried at room temperature in the dark to obtain the finished ultrafiltration membrane containing only carbon, hydrogen, and oxygen elements.
[0028] The ultrafiltration membrane prepared in Example 1 was tested, and its performance is as follows: the pure water flux at 20°C under a pressure of 0.1 MPa is 1800 L / m³. 2 The membrane has a bubble point of 0.14 MPa in water, a pure water contact angle of 8°, a PEG rejection rate of 96.5% for a molecular weight of 50,000 Da, and a bovine serum albumin rejection rate of over 99.8%. Elemental analysis shows that the membrane support layer contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 3 / 3 / 1, and the separation layer also contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 26 / 15 / 6. When the ultrafiltration membrane is burned in oxygen, analysis shows that the burning products are only CO2 and H2O.
[0029] Example 3
[0030] Take 22g of EVOH (ethylene molar content 35%, melt index 1.9g / 10min) from Changchun Chemical Co., Ltd., add it to 100g of DMAC, heat and stir to dissolve. Then, add 4g of stearic acid, 0.3g of hydrochloric acid, and 0.4g of anhydrous sodium sulfate in sequence, stir evenly, and then introduce dry nitrogen gas. Raise the temperature to 140℃ and react for 8 hours. Then, filter all the substances together through an activated carbon filter to obtain a clear and transparent polymer solution. Take 100g of polymer solution, add 2.5g of polyvinylpyrrolidone and 0.15g of Tween-80, stir evenly, and let stand to remove bubbles to obtain a clear and transparent casting solution. The casting solution is coated onto a PET nonwoven fabric to form a uniform liquid film, which is then placed in a pure water coagulation bath at 25°C. After solution phase inversion, an ultrafiltration membrane with a thickness of 120 μm is obtained. The ultrafiltration membrane is then rinsed with pure water and soaked in alcohol to remove residual pore-forming agents, surfactants, solvents, unreacted saturated fatty acids, and catalysts. Finally, it is air-dried at room temperature in the dark to obtain the finished ultrafiltration membrane containing only carbon, hydrogen, and oxygen elements.
[0031] The ultrafiltration membrane prepared in Example 1 was tested, and its performance is as follows: the pure water flux at 20°C under a pressure of 0.1 MPa is 1400 L / m³. 2 The membrane has a bubble point of 0.15 MPa in water, a pure water contact angle of 15°, a PEG rejection rate of 98.3% for a molecular weight of 50,000 Da, and a bovine serum albumin rejection rate of over 99.9%. Elemental analysis shows that the membrane support layer contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 9 / 6 / 4, and the separation layer also contains only carbon, hydrogen, and oxygen in a ratio of C / H / O = 37 / 19 / 9. When the ultrafiltration membrane is burned in oxygen, analysis shows that the burning products are only CO2 and H2O.
[0032] Comparative Example 1
[0033] The difference from Example 1 is that the desiccant anhydrous sodium sulfate was not added; otherwise, they are exactly the same.
[0034] The ultrafiltration membrane prepared in Comparative Example 1 was tested, and the results are as follows: the pure water flux at 20℃ and a pressure of 0.1 MPa was 2400 L / m³. 2The membrane's bubble point in water was 0.01 MPa, its contact angle with pure water was 11°, and its rejection rate for PEG (50,000 Da) was 14.3%, while its rejection rate for bovine serum albumin (BSA) was 20.5%. Elemental analysis showed that the membrane's support layer contained only carbon, hydrogen, and oxygen in a ratio of C / H / O = 9 / 6 / 4, and the separation layer also contained only carbon, hydrogen, and oxygen in a ratio of C / H / O = 27 / 13 / 6. Burning the ultrafiltration membrane in oxygen revealed only CO2 and H2O as combustion products. The test results clearly show a significant deterioration in the membrane's bubble point and rejection rate. This is because the absence of a desiccant prevents the complete removal of water generated during the esterification reaction, hindering further esterification and resulting in a lower degree of esterification of EVOH. This negatively impacts the entire membrane fabrication process. Furthermore, the un-esterified saturated fatty acids form large pores on the membrane surface during subsequent membrane formation, affecting membrane performance.
[0035] Comparative Example 2
[0036] The difference from Example 1 is that the thickness of the prepared ultrafiltration membrane is 130 μm, but everything else is exactly the same.
[0037] The ultrafiltration membrane prepared in Comparative Example 2 was tested, and the results are as follows: the pure water flux at 20℃ and a pressure of 0.1 MPa was 190 L / m³. 2 The membrane's bubble point in water was 0.24 MPa, its contact angle with pure water was 12°, and it exhibited a 98.5% rejection rate for PEG with a molecular weight of 50,000 Da and a rejection rate of over 99.9% for bovine serum albumin. Elemental analysis showed that the membrane's support layer contained only carbon, hydrogen, and oxygen in a ratio of C / H / O = 9 / 6 / 4, and the separation layer also contained only carbon, hydrogen, and oxygen in a ratio of C / H / O = 29 / 14 / 7. Burning the ultrafiltration membrane in oxygen revealed only CO2 and H2O as combustion products. These test results clearly show that while the membrane skin thickness increased by approximately 50%, other properties remained largely unchanged, but the flux decreased significantly. This is because the increased skin thickness greatly increases the resistance to water permeation, leading to a decrease in flux.
Claims
1. A method for preparing an environmentally friendly water treatment ultrafiltration membrane, characterized in that... The support layer of the ultrafiltration membrane is composed of a thermoplastic polyester nonwoven fabric or inner liner containing only carbon, hydrogen, and oxygen elements, and the functional layer is composed of a polymer containing only carbon, hydrogen, and oxygen elements; the preparation method includes the following steps: S1: Ethylene-vinyl alcohol copolymer (EVOH) is used as a reaction raw material. It is heated and stirred in a solvent to dissolve it. Then, saturated fatty acids, catalysts and desiccants are added. Dry nitrogen gas is introduced and the temperature is raised to carry out an esterification reaction, generating a high molecular weight ester compound containing only carbon, hydrogen and oxygen elements. After the reaction is completed, all substances are filtered together through an activated carbon filter to remove the desiccant and impurities, and a clear and transparent high molecular weight ester compound solution is obtained. The ethylene molar content in the EVOH is between 30% and 40%, and the melt index is less than 2 g / 10 min; the saturated fatty acid is one of lauric acid, palmitic acid, and stearic acid; the esterification reaction temperature is between 130 and 170 °C, and the reaction time is 6 to 8 hours. S2: Add pore-forming agent and surfactant to the above polymer ester compound solution, stir evenly to obtain a clear and transparent casting solution, let the casting solution stand to remove bubbles and then use it. S3: The above casting solution is coated onto a support layer composed of thermoplastic polyester nonwoven fabric or inner lining tube containing only carbon, hydrogen and oxygen elements to form a uniform liquid film. Then, it is placed in a coagulation bath and an ultrafiltration membrane is obtained through solution phase inversion. After rinsing with pure water, the ultrafiltration membrane is immersed in alcohol to remove residual pore-forming agents, surfactants, solvents, unreacted saturated fatty acids and catalysts. Then, it is naturally dried in the dark to obtain an environmentally friendly water treatment ultrafiltration membrane.
2. The method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The thermoplastic polyester is one of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).
3. The method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The solvent mentioned in S1 is one of N,N-dimethylacetamide (DMAC) and N-methylpyrrolidone (NMP).
4. The method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The catalyst mentioned in S1 is one of p-toluenesulfonic acid, camphorsulfonic acid, and hydrochloric acid; the desiccant mentioned in S1 is one of anhydrous sodium sulfate and 4A molecular sieve.
5. A method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The mass fractions of each substance used in the esterification reaction described in S1 are as follows: solvent 100 parts, EVOH 20-23 parts, saturated fatty acid 3-5 parts, catalyst 0.2-0.5 parts, and desiccant 0.5-1 parts.
6. The method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The porogen mentioned in S2 is one of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG); the surfactant is one of Tween-80 and Span-60; the mass ratio of the porogen, surfactant and polymer ester compound solution is (2-3): (0.1-0.2):
100.
7. A method for preparing an environmentally friendly water treatment ultrafiltration membrane according to claim 1, characterized in that, The coagulation bath described in S3 is pure water at 20-30 °C.
8. An environmentally friendly water treatment ultrafiltration membrane prepared by the preparation method according to any one of claims 1-7, wherein the support layer of the ultrafiltration membrane is composed of a thermoplastic polyester nonwoven fabric or inner liner containing only carbon, hydrogen and oxygen elements, and the functional layer is composed of a polymer containing only carbon, hydrogen and oxygen elements.
9. The environmentally friendly water treatment ultrafiltration membrane as described in claim 8, wherein the thickness of the ultrafiltration membrane is 80-120 μm.
Citation Information
Patent Citations
Biodegradable oil-water separation net film with super-hydrophobic and super-oleophylic properties and preparation method thereof.
CN103157392A
Preparation method of multifunctional biodegradable oil-water separation film
CN107812453A
Biodegradable inorganic-organic composite film and preparation method thereof
CN113457463A
Semipermeable membrane
JP1992190836A
Carbonic acid-esterified ethylene-vinyl alcohol copolymer and its production
JP1998158326A
